Students’ Ability in Writing Recount Text at The Second Grade Students of MTS Bai’aturridhwan Bukittinggi - Tsuraya Pratiwi, Anna; Syandri, Gusmaizal; Syam, Erlinda (Journal of Educational Management and Strategy, 2023)
Recount text is a type of text taught in English subjects at the junior high school or MTs level. This research aims to determine students' abilities in writing recount text. Data was obtained through a writing test given to students. The students' writing results were then examined by looking at five components, namely content, organization, grammar, vocabulary and mechanics. The data was then described using qualitative methods. The research results show that students' ability to write recount text is low. This can be seen from the average score between 56 and 65. This proves that students still experience difficulties in writing, so the quality of their writing is less than satisfactory. Abstrak Teks recount adalah salah satu jenis teks yang diajarkan pada mata Pelajaran Bahasa Inggris pada tingkat SMP atau MTs. Penelitian ini bertujuan untuk mengetahui kemampuan siswa dalam menulis teks recount. Data didapatkan melalui tes menulis yang diberikan pada siswa . Hasil menulis siswa lalu diteliti dengan  melihat lima komponen, yaitu content, organization, grammar, vocabularies dan mechanics. Data lalu diseskripsikan dengan menggunakan metode kualitatif. Hasil penelitian menunjukkan bahwa kemampuan siswa dalam menulis teks recount adalah rendah. Ini terlihat dari perolehan nilai rata-rata antara 56 sampai dengan 65. Hal ini membuktikan bahwa siswa masih mengalami kesulitan dalam menulis, sehingga kualitas tulisannya kurang memuaskan.